Creative Intelligence In Forming Student Character - Haniah, St; Nursalam, Nursalam; Hamid, Wahyuddin (Journal Research of Social Science, Economics, and Management, 2023)
School community which includes components of knowledge, awareness or will, and actions to carry out these values. In character education in schools, all components (education stakeholders) must be involved, including the components of education itself, namely curriculum content, learning and assessment processes, handling or management of subjects, school management, implementation of extracurricular activities or activities, empowerment of infrastructure, financing, and work ethic of all members of the school/environment. The application of creative intelligence as an effort to make it easier to shape the character of students. Creative intelligence is the mental capacity to concoct new and better ideas and ways to do things and juxtapose concepts, and to perceive and think with greater freedom and less constraint by past experience and learned ideas than usual. Along with these analytical and practical capacities are parts of the triarchal intelligence theory. Then the applied creative intelligence will make character formation easier to form with new learning situations and the readiness of students to accept student character formation.